The role of genetic variation in VKORC1 and GGCX on warfarin response in a South African population - Cindi, Zinhle (Department of Pathology, 2019)
Background: Warfarin is the most commonly used drug in the management of thromboembolic disease. However, there is a huge variability in the management of warfarin affecting the international normalized ratio (INR). Many genetic-association studies have reported on European and Asian populations which has led to the designing of specific algorithms that are now being used to assist in warfarin dosing. However, very few or no studies have looked at the pharmacogenetics of warfarin in African populations, yet, huge differences in dosage requirements to reach the same INR have been observed. We set out to investigate genetic factors affecting warfarin therapy in South African black (SAB) and Mixed Ancestry (MA) participants. Methods: We recruited consenting participants from Groote Schuur Hospital and Gugulethu Community Health Centre comprising 263 of Mixed Ancestry (MA) descent and 109 of South African black (SAB) descent. Demographic data, clinical information and 5 ml of blood for genetic characterization was obtained from participants. DNA was extracted from the blood and genotyped using PCR/RFLP and Sanger sequencing for 5 single nucleotide polymorphisms (SNPs), VKORC1 c.-1639G>A, VKORC1 c.1173C>T, VKORC1 c.3730G>A, GGCX c.1218C>T and GGCX c.1242C>T. Results: We report an association of age with warfarin dose, where, older patients had lower dose requirements (p>0.001 in MA; p>0.042 in SAB). Higher BMI was associated with increased stabilizing dose in the MA group (p=0.003). The SNP VKORC1 c.-1639G>A was associated with stabilizing dose only in MA (p>0.003), with carriers of the A/A genotype requiring lower dosages (18 ± 14 mg/week) compared to G/G (38 ± 14 mg/week). Conclusion: We conclude that environmental and genetic factors may play a role in the way South African patients respond to warfarin. Particularly, it appears as if MA and SAB population group have different underlying genetic markers for warfarin response. This knowledge in warfarin pharmacogenomics could help in the judicious use of warfarin in South African patients. However, more genetic markers need to be characterized to understand the profiles of genetic determinants affecting responses to warfarin therapy in world populations.